2007
DOI: 10.1007/s10745-006-9101-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Inductive and Deductive Modeling of Land Use Decisions: Principles, a Model and an Illustration from the Philippines

Abstract: Understanding the causes of land use change is of great importance for issues of tropical deforestation, agricultural development and biodiversity conservation. Many quantitative studies, therefore, aim to link land use change to its causal 'driving forces.' The epistemology of virtually all these studies is inductive, searching for correlations within relatively large, sometimes spatially explicit, datasets. This can be sound science but we here aim to exemplify that there is also scope for more deductive app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…For example, Rudel's sociological perspective on urban sprawl and tropical deforestation emphasizes the role of strategic actions by states and coalitions of interested parties in transforming landscapes, and identifies agents of change and the timing of transformative events (Rudel 2009). Overmars et al (2007a) formalize the explanation of human decision and action in the environmental field with the action-in-context (AiC) framework. The sociological and political economy approach can be especially powerful for land change research in combination with the economic approach (e.g., Walker et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rudel's sociological perspective on urban sprawl and tropical deforestation emphasizes the role of strategic actions by states and coalitions of interested parties in transforming landscapes, and identifies agents of change and the timing of transformative events (Rudel 2009). Overmars et al (2007a) formalize the explanation of human decision and action in the environmental field with the action-in-context (AiC) framework. The sociological and political economy approach can be especially powerful for land change research in combination with the economic approach (e.g., Walker et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The second activity, which we here call 'predictive modelling' (Shmueli 2010), instead presumes that a model describing the relationship of interest is already known, as are observed or estimated values of the relevant predictor variables, and therefore combines these to predict previously unknown values of the biodiversity response variable. The model used to make such predictions can be either an 'inductive model' derived through data analysis, in which case the activities of data analysis and prediction are integrally linked, or a 'deductive model' built directly from existing expert knowledge of the relationship between response and predictor variables (Corsi et al 2000;Overmars et al 2007;Tuanmu and Jetz 2014).…”
Section: Broad Roles Of Modelling In Biodiversity Assessmentmentioning
confidence: 99%
“…A deductive (theory-driven) approach, on the other hand, is strong in explaining how and why land use will change (which is process resemblance), but is weak in spatial allocation of land-use change (Overmars, de Groot & Huigen, 2007). Overmars et al (2007) have shown that prediction of spatial location with deductive models is promising when compared to inductive models. For land-use change developments that follow a single dominant process it is expected that a deductive model will score only marginally less on spatial resemblance than an inductive model (see Fig.…”
Section: Lessons From Model Validationmentioning
confidence: 99%